2012
DOI: 10.9775/kvfd.2011.5648
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Pestivirus and Rift Valley Fever Virus Infections in Aborted Ruminant Foetuses in the Blacksea Region in Turkey

Abstract: SummaryIn this study, aborted foetuses (cattle, sheep and goat) in either coastal or inland Blacksea region of Turkey were surveyed for the presence of nucleic acids from pestiviruses (bovine viral diarrhoea virus-BVDV, border disease virus-BDV) and rift valley fever virus (RVFV) by reverse transcriptase polymerase chain reaction assay (RT-PCR). Pestivirus nucleic acids were found in 39 of 53 aborted calves (73.6%), in 34 of 37 aborted lambs (91.9%) and in 2 of 2 aborted kids (100%) by RT-PCR. In addition RVFV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
7
0
3
Order By: Relevance
“…Review articles that present general or agent‐specific information on vector‐borne infections in Turkey including phleboviruses comprised 7 of the entries, and they were examined for further cited research on phleboviruses. Two reports presented surveillance data on the mosquito‐borne pathogenic phlebovirus Rift Valley fever virus, where serological and nucleic acid tests gave negative results in 350 sera (from cattle, horse, sheep, goat, and water buffaloes) and in aborted fetuses, collected from the Black Sea region of Turkey.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Review articles that present general or agent‐specific information on vector‐borne infections in Turkey including phleboviruses comprised 7 of the entries, and they were examined for further cited research on phleboviruses. Two reports presented surveillance data on the mosquito‐borne pathogenic phlebovirus Rift Valley fever virus, where serological and nucleic acid tests gave negative results in 350 sera (from cattle, horse, sheep, goat, and water buffaloes) and in aborted fetuses, collected from the Black Sea region of Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 1693 database entries that comprise 1491 (88.1%) international and 202 (11.9%) regional reports were accessed. Following the omission of repetitive and/or unrelated records, 42 manuscripts emerged . A detailed assessment of content in this cohort revealed that 2 reports were merely focusing on West Nile virus without presenting data on phleboviruses and were subsequently omitted .…”
Section: Resultsmentioning
confidence: 99%
“… 44 Additionally, it is possible that RVFV-carrying vectors could travel to EU via the Middle East, particularly through Turkey. 45 However, RVFV remains non-existent or undetected in Turkey at present. 45 Assuming that this is a viable pathway, the risk of dissemination to the EU would be elevated during epidemic periods.…”
Section: Introduction Of Rvfv To Previously Unaffected Regionsmentioning
confidence: 99%
“… 45 However, RVFV remains non-existent or undetected in Turkey at present. 45 Assuming that this is a viable pathway, the risk of dissemination to the EU would be elevated during epidemic periods. 36 In comparison, it is highly unlikely that a vector could traverse the Atlantic Ocean to the US via natural wind dispersal, even in hurricane winds.…”
Section: Introduction Of Rvfv To Previously Unaffected Regionsmentioning
confidence: 99%
“…Limited research has been carried out on RVFV in Turkey. In their study on ruminant unborn fetus and many various species of domestic farm animals around northern areas of Turkey, Albayrak and Ozan [28,29] did not encounter any RVF infection. Yılmaz et al [30] found RVF infection seronegative in their study on sheep around Kars region.…”
Section: Discuss the Implication Of Distribution Of Positivitymentioning
confidence: 99%